Evaluation of land suitability for citrus cultivation in Khana Local Government Area of Rivers State, Southern Nigeria - Kaananwii Dum Peter; Aigboghosa Samson Umweni (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2021)
Soils of Khana Local Government Area of Rivers State, Southern Nigeria were evaluated using semi detailed soil survey for citrus cultivation. The purpose of this research was to evaluate the suitability of soils of the study area for the cultivation of citrus. The total land area covers 49,631.54 ha and was delineated into eight mapping units based on the soil types. One pedon each was dug in each mapping unit and described using the FAO system. The nonparametric method of soil suitability evaluation was used. Four soil orders, majorly Inceptisols/Cambisols, Entosols/Arenosols, Ultisols/Acrisols, and Alfisols/Lixisols, were identified in the area. The results showed that land requirements/characteristics such as climate (mean annual rainfall), wetness (depth to water table) and fertility made the land marginally suitable (S3) to not suitable (N) for citrus cultivation across the eight pedons. The three limitations for citrus cultivation in the area are climate (annual rainfall), wetness (depth to the water table) and fertility (low status of NPK and pH). The land is potentially suitable for citrus cultivation but currently marginally and not suitable due to these three limitations.